A PID-based algorithm to guarantee QoS delay requirements in LR-PONs - Jiménez, Tamara; Merayo, Noemí; Durán, Ramón J.; Fernández, Patricia; de Miguel, Ignacio; Aguado, Juan C.; Lorenzo, Rubén M.; Abril, Evaristo J. (Optical switching and networking, 2014)
In this paper a novel algorithm with delay guarantees for high priority traffic based on a Proportional (P) controller for Long-Reach Passive Optical Networks (LR-PONs) is proposed. We have recently demonstrated that Proportional–Integral–Derivative (PID) controllers are quite effective when controlling guaranteed bandwidth levels and in this paper this functionality is adapted to jointly deal with Class of Service (CoS) and client differentiation in order to fulfill delay requirements. Therefore, it leads to an efficient control of the mean packet delay which enhances the provided Quality of Service (QoS) inside the LR-PON. Simulation results have exhibited that the bandwidth allocation process made by the P controller achieves this objective faster than other existing proposals. In fact, it stabilizes the priority delays in less than 2min comparing with 5 or 6min obtained by other proposals. Furthermore, it has been demonstrated that its performance is more robust than other proposals since it is independent of the initial network conditions, adapting very efficiently the available resources in order to comply with the established delay bounds of the most restrictive services.